Sphingosine-1 phosphate receptor (S1p1), a critical receptor controlling human lymphocyte trafficking, is expressed in hen and human ovaries and ovarian tumors - Bradaric Michael J; Barua Animesh; Penumatsa Krishna; Yi Yu; Edassery Seby L; Sharma Sameer; Abramowicz Jacques S; Bahr Janice M; Luborsky Judith L (BMC, 2011)
Abstract Background Sphingosine-1 receptor 1 (S1P1) plays a major role in regulating lymphocyte egress from peripheral lymph tissue. Lymphocyte trafficking is potentially a critical response to tumors and to tumor vaccines. Also, the receptor has been shown to influence metastasis. However, there is little information on its expression in the aged ovary or ovarian tumors. As a basis for further studies in the laying hen model of spontaneous ovarian cancer, the objective of this study was to determine if S1P1 is expressed in hens, and if the morphological distribution of S1P1 is similar in hen and human ovary and ovarian tumors. Methods S1P1 mRNA was ascertained in hen tissue by RT-PCR using hen specific primers. S1P1 protein expression and localization was evaluated in hen and human tissue with a human S1P1 antibody by Western blot and immunohistochemistry. Results S1P1 mRNA was expressed in all hen tissues examined. Protein was detected in human and hen ovary and ovarian tumors at 47, 72 and 108 kDa in Western blots. S1P1 was similarly expressed on endothelial cells, lymphocytes and surface epithelial cells in normal ovaries and tumor-containing ovaries of the hen. In addition, S1P1 distribution was heterogeneous in both hen and human ovarian tumors by immunohistochemistry. Conclusion The results show that S1P1 is expressed in the hen and human ovary as well as in ovarian tumors. These findings support the use of the hen in further studies of the role of S1P1 in metastasis and immune cell trafficking in ovarian tumor development.